Dairy consumption and CVD: a systematic review and meta-analysis. Issue 4 (20th January 2016) - Alexander, Dominik D.; Bylsma, Lauren C.; Vargas, Ashley J.; Cohen, Sarah S.; Doucette, Abigail; Mohamed, Muhima; Irvin, Sarah R.; Miller, Paula E.; Watson, Heather; Fryzek, Jon P.
Abstract: Inverse associations between dairy consumption and CVD have been reported in several epidemiological studies. Our objective was to conduct a meta-analysis of prospective cohort studies of dairy intake and CVD. A comprehensive literature search was conducted to identify studies that reported risk estimates for total dairy intake, individual dairy products, low/full-fat dairy intake, Ca from dairy sources and CVD, CHD and stroke. Random-effects meta-analyses were used to generate summary relative risk estimates (SRRE) for high v . low intake and stratified intake dose–response analyses. Additional dose–response analyses were performed. Heterogeneity was examined in sub-group and sensitivity analyses. In total, thirty-one unique cohort studies were identified and included in the meta-analysis. Several statistically significant SRRE below 1.0 were observed, namely for total dairy intake and stroke (SRRE=0·91; 95 % CI 0·83, 0·99), cheese intake and CHD (SRRE=0·82; 95 % CI 0·72, 0·93) and stroke (SRRE=0·87; 95 % CI 0·77, 0·99), and Ca from dairy sources and stroke (SRRE=0·69; 95 % CI 0·60, 0·81). However, there was little evidence for inverse dose–response relationships between the dairy variables and CHD and stroke after adjusting for within-study covariance. The results of this meta-analysis of prospective cohort studies have shown that dairy consumption may be associated with reduced risks of CVD, although additional data are needed to more comprehensively examine potential dose–response patterns.